2021
DOI: 10.1101/2021.10.14.464473
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell Networks Reorganise to Facilitate Whole-brain Supercritical Dynamics During Epileptic Seizures

Abstract: Excitation-inhibition (EI) balance may be required for the organisation of brain dynamics to a phase transition, criticality, which confers computational benefits. Brain pathology associated with EI imbalance may therefore occur due to a deviation from criticality. However, evidence linking critical dynamics with EI imbalance-induced pathology is lacking. Here, we studied the effect of EI imbalance-induced epileptic seizures on brain dynamics, using in vivo whole-brain 2-photon imaging of GCaMP6s larval zebraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 98 publications
(124 reference statements)
0
4
0
Order By: Relevance
“…It might be that a potential alteration of the regional excitation/inhibition (E/I) balance could facilitate the recruitment of a given brain region by the ongoing transient large‐scale perturbations. In the same line of thinking, Burrows et al 50 observed that manipulating the E/I balance in cellular, in vivo neural networks caused a shift of the operational regimen away from criticality, which was linked, in turn, to the emergence of epileptic activity. Beyond the neuroscientific implications, our methodology might directly help the patients' management.…”
Section: Discussionmentioning
confidence: 98%
“…It might be that a potential alteration of the regional excitation/inhibition (E/I) balance could facilitate the recruitment of a given brain region by the ongoing transient large‐scale perturbations. In the same line of thinking, Burrows et al 50 observed that manipulating the E/I balance in cellular, in vivo neural networks caused a shift of the operational regimen away from criticality, which was linked, in turn, to the emergence of epileptic activity. Beyond the neuroscientific implications, our methodology might directly help the patients' management.…”
Section: Discussionmentioning
confidence: 98%
“…It might be that a potential alteration of the regional excitation/inhibition (E/I) balance could facilitate the recruitment of a given brain region by the ongoing transient large-scale perturbations. In the same line of thinking, Burrows and colleagues (Burrows et al, 2021) observed that manipulating the E/I balance in cellular in vivo neural networks caused a shift of the operational regime away from criticality which was linked, in turn, to the emergence of epileptic activity. Beyond the neuroscientific implications, our methodology might directly help the patients’ management.…”
Section: Discussionmentioning
confidence: 97%
“…However a significant limitation of point-scanning 2-photon microscopy is speed, since it scans the tissue 1 voxel at a time. With recent implementation of resonant scanning mirrors, imaging speeds have been achieved of 1–1.2 Hz for 9 to 12 planes over 76 μm (Andalman et al, 2019 ), 2.7 Hz for 10 planes over 150 μm (Burrows et al, 2021 ), and 9.7 Hz for 5 planes of just the tectum (Sainsbury et al, 2023 ). In 2-photon light-sheet microscopy the light sheet consists of 2-photon excitation generated by scanning a pulsed infrared laser source (Truong et al, 2011 ; Wolf et al, 2015 ).…”
Section: The Zebrafish Model Systemmentioning
confidence: 99%